2008
DOI: 10.1080/14675980802078525
|View full text |Cite
|
Sign up to set email alerts
|

Asian students’ perceptions of group work and group assignments in a New Zealand tertiary institution

Abstract: This study, conducted in 2005 in a New Zealand tertiary institution, examines Asian students' perceptions of the much-promulgated cooperative learning concepts in the form of group work and group assignments. Twenty-two Asian students participated in one-hour individual face-to-face semi-structured interviews. The study found that Asian students valued highly the significance of classroom group discussions where they could interact with students from other cultures and backgrounds, improve their English-langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 19 publications
2
53
2
Order By: Relevance
“…problem solving, critical thinking, communication and leadership skills. This finding is supported by Li and Campbell (2008) who indicated that most Asians students highly valued the significance of classroom group discussions where they could interact with students from other cultures and backgrounds. However this finding is in contradiction to Dean (2005) that critical thinking is discouraged in Pakistani schools.…”
Section: Discussionsupporting
confidence: 74%
“…problem solving, critical thinking, communication and leadership skills. This finding is supported by Li and Campbell (2008) who indicated that most Asians students highly valued the significance of classroom group discussions where they could interact with students from other cultures and backgrounds. However this finding is in contradiction to Dean (2005) that critical thinking is discouraged in Pakistani schools.…”
Section: Discussionsupporting
confidence: 74%
“…Research was done into Chinese students' 'satisfaction of learning experience' (educational quality, programme offering, and learning support) (Campbell & Li, 2007;Li & Campbell, 2008), 'service quality' experience (administrative support, academic staff quality, campus quality, curriculum quality, qualification integrity, personal compatibility, and 'evaluations' of the overseas study experience (Simpson & Tan, 2008). This kind of feedback from the Chinese students will stimulate the New Zealand authorites to make the necessary modifications, in order to keep a leading role in recruiting Chinese students in the competitive international market.…”
Section: Notementioning
confidence: 99%
“…Montgomery (2009) found that student's views on working in multicultural groups with an "AfL approach" 1 were more positive than a decade ago and perceived as adding value to their learning experience. Others (see for instance Li and Campbell 2008) reported negative perceptions of students to intercultural group work.…”
mentioning
confidence: 99%